2020
DOI: 10.1177/0144598720930424
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of oil price on exchange rates: Evidence from Saudi Arabia

Abstract: The real exchange rate is a key indicator of a country’s trade competitiveness in the world. This paper investigates the interaction between oil price and real exchange rates in Saudi Arabia during the period January 1986 -March 2019, using monthly data. This study uses the autoregressive distributed lag model and the error correction model in order to investigate the existence of a long-run equilibrium relationship between the variables. The evidence reveals that there is a strong long-run cointegrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…According to the literature, variations in oil prices have a powerful influence on various economic variables [7][8][9][10][11]. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, variations in oil prices have a powerful influence on various economic variables [7][8][9][10][11]. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some empirical papers have tested the effect of oil prices on energy consumption and the level of carbon dioxide emissions. In this regard, [11] suggested that there was a causality interaction from oil price to energy consumption in Tunisia, while [12] found that the oil price had a significant influence on energy consumption in China. [13] tested the causal linkage between oil price and the level of carbon emissions using the ARDL model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the literature, the variations of oil prices have a significant impact on various economic variables. In this regard: [ 4 7 ] have indicated that the effect of the oil prices on economic indexes in developed and developing countries can be different; these different findings can be attributed to various economic factors for instance: (oil-importing countries vs oil-exporting countries). Increases in oil prices can be economically bad for oil-importing countries but it is economically good news for oil-exporting countries.…”
Section: Introductionmentioning
confidence: 99%
“…First, the article aims to test the impact of oil prices on the real estate market. According to the literature, the variations of oil prices have a significant influence on various economic variables [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation